Filtered cathodic vacuum arc deposition of metal nitrides - Ji, Xiaohong (2009)
The numerous applications of group III nitride semiconductors have attracted significant research interest over the last decade. A novel ion-beam assisted filtered cathodic vacuum arc (I-FCVA) technique has been developed to fabricate III nitrides using pure metallic target as metal source. For the first time, FCVA technique is capable of handling low melting point metal target such as Ga and In. Binary III nitrades (AIN, GaN, InN) on Si subtrates have been fabricated, characterized and analyzed.